2019
DOI: 10.3390/jcm8122039
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Low-Molecular-Weight Heparin for Thrombosis Prophylaxis: Systematic Review with Meta-Analysis and Trial Sequential Analysis

Abstract: International guidelines recommend low-molecular-weight heparin (LMWH) as first-line pharmacological option for the prevention of venous thromboembolism (VTE) in many patient categories. Guidance on the optimal prophylactic dose is lacking. We conducted a systematic review with meta-analysis and trial sequential analysis (TSA) of randomized controlled trials to assess benefits and harms of low-dose LMWH versus placebo or no treatment for thrombosis prophylaxis in patients at risk of VTE. PubMed, Cochrane Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…After a median follow-up period of 3.5 months, VTE occurred in 1.2% of the semuloparin group and 3.4% of the placebo group with a number needed to treat (NNT) of 45.5 and clinically relevant bleeding occurring in 2.8% of patients receiving semuloparin versus 2.0% receiving placebo [ 17 ]. Other studies of LMWH in unselected patients have similarly found NNTs in the 40–50 range [ 17 , 18 , 19 , 20 , 21 ]. When cancer patients at high risk of VTE (Khorana score of three or greater) were selected, LMWH thromboprophylaxis reduced the VTE incidence (12% in LMWH group versus 21% in observation group) but resulted in a seven-fold increase risk of bleeding [ 21 ].…”
Section: Historic and Current Approaches To Patient Selection For mentioning
confidence: 86%
See 1 more Smart Citation
“…After a median follow-up period of 3.5 months, VTE occurred in 1.2% of the semuloparin group and 3.4% of the placebo group with a number needed to treat (NNT) of 45.5 and clinically relevant bleeding occurring in 2.8% of patients receiving semuloparin versus 2.0% receiving placebo [ 17 ]. Other studies of LMWH in unselected patients have similarly found NNTs in the 40–50 range [ 17 , 18 , 19 , 20 , 21 ]. When cancer patients at high risk of VTE (Khorana score of three or greater) were selected, LMWH thromboprophylaxis reduced the VTE incidence (12% in LMWH group versus 21% in observation group) but resulted in a seven-fold increase risk of bleeding [ 21 ].…”
Section: Historic and Current Approaches To Patient Selection For mentioning
confidence: 86%
“…After a median follow-up period of 3.5 months, VTE occurred in 1.2% of the semuloparin group and 3.4% of the placebo group with a number needed to treat (NNT) of 45.5 and clinically relevant bleeding occurring in 2.8% of patients receiving semuloparin versus 2.0% receiving placebo [17]. Other studies of LMWH in unselected patients have similarly found NNTs in the 40-50 range [17][18][19][20][21].…”
Section: Historic and Current Approaches To Patient Selection For Primary Thromboprophylaxis Of Cancer-associated Thrombosismentioning
confidence: 92%
“…5 6 7 8 9 We previously distinguished between low, intermediate, and high dose low-molecular-weight heparin based on the summary of product characteristics and randomised controlled trial dosing regimens. 10 11 A network meta-analysis on prophylaxis in surgical patients found different intervention effects for different prophylactic low-molecular-weight heparin doses. 12 Additionally, a Cochrane meta-analysis in patients with covid-19 found no conclusive benefits of high dose low-molecular-weight heparin or unfractionated heparin over lower doses.…”
Section: Introductionmentioning
confidence: 99%
“…Pentasaccharides have been studied and registered for venous thromboembolism prevention in a single dose, but low-molecular-weight heparin and unfractionated heparin can be administered in several doses depending on the country and setting 56789. We previously distinguished between low, intermediate, and high dose low-molecular-weight heparin based on the summary of product characteristics and randomised controlled trial dosing regimens 1011. A network meta-analysis on prophylaxis in surgical patients found different intervention effects for different prophylactic low-molecular-weight heparin doses 12…”
Section: Introductionmentioning
confidence: 99%
“… 14 During the current COVID-19 pandemic, several prophylactic doses and types of LMWH are being used worldwide; however, there are no high-quality evidence studies or recommendation for the optimal prophylactic LMWH dose. 15 …”
Section: Introductionmentioning
confidence: 99%